Probing the Evolution of Retained Austenite in TRIP Steel During Strain-Induced Transformation: A Multitechnique Investigation - Haidemenopoulos, G. N.; Constantinou, Marios; Kamoutsi, H.; Krizan, Daniel; Bellas, I.; Koutsokeras, Loukas E.; Constantinides, Georgios (My University, 2018)
X-ray diffraction analysis, magnetic force microscopy, and the saturation magnetization method have been employed to study the evolution of the percentage and size of retained austenite (RA) particles during strain-induced transformation in a transformation-induced plasticity (TRIP) steel. A low-alloy TRIP-700 steel with nominal composition Fe-0.2C-0.34Si-1.99Mn-1Al (mass%) was subjected to interrupted tensile testing at strain levels of 0–22% and the microstructure subsequently studied. The results of the three experimental techniques were in very good agreement regarding the estimated austenite volume fraction and its evolution with strain. Furthermore, this multitechnique approach revealed that the average particle size of RA reduced as the applied strain was increased, suggesting that larger particles are less stable and more susceptible to strain-induced phase transformation. Such experimentally determined evolution of the austenite size with strain could serve as an input to kinetic models that aim to predict the strain-induced transformation in low-alloy TRIP steels.
Keywords: Transformation Induced; Plasticity Steel; Manganese Steel; Austenite